Feasibility of percutaneous endoscopic gastrostomy insertion in children receiving peritoneal dialysis. Issue 5 (September 2022) - Kempf, Caroline; Holle, Johannes; Berns, Susanne; Henning, Stephan; Bufler, Philip; Müller, Dominik
Background: Peritoneal dialysis (PD) is the preferred dialysis modality for paediatric patients with end-stage kidney disease. Frequently, malnutrition is encountered. Percutaneous endoscopic gastrostomy (PEG) is the preferred mode of feeding because of its minimal invasive mode of placement and easy handling in daily life. However, reports of a high risk for early post-interventional peritonitis hampered this procedure during PD and controlled studies on the benefit of peri-interventional management to prevent peritonitis are lacking. Here, we report the safety profile of PEG insertion among a cohort of children on PD by using a prophylactic antibiotic and antifungal regimen as well as modification of the PD programme. Methods: We performed a single-centre analysis of paediatric PD patients receiving PEG placement between 2015 and 2020. Demographic data, peri-interventional prophylactic antibiotic and antifungal treatment as well as modification of the PD programme were gathered and the incidence of peritonitis within a period of 28 days after PEG was calculated. Results: Eight PD patients (median weight 6.7 kg) received PEG insertion. Antibiotic and antifungal prophylaxis were prescribed for median time of 4.0 and 5.0 days, respectively. After individual reduction of PD intensity, all patients continued their regular PD programme after a median of 6 days. One patient developed peritonitis within 24 h after PEG insertion and simultaneous surgery for hydrocele. Conclusions: Applying an antibiotic and antifungal prophylactic regime as well as an adapted PD programme may reduce the risk for peritonitis in paediatric PD patients who receive PEG procedure.